Islamic Religious Education for Family and Community - Eva Sri Rohani; Wahyuni Wahyuni; Nuramin Nurdin; Julkarnain Julkarnain; Muhammad Tang; Juhasdi Susono (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This article discusses the relationship between Islamic Religious Education (PAI) and Education, which cannot be separated from family, school, and community life. Education aims to teach humans to possess knowledge and skills accompanied by faith and piety toward Allah SWT, so that they will utilize the knowledge and skills they have for the good of society, the environment, and their nation. This research uses the library research method. Library research aims to understand, analyze, and evaluate concepts and theories relevant to the discussed topic, namely the role of Islamic religious education in families and communities. The study results show that Islamic religious education within the family and community, particularly in shaping social, moral, and spiritual values. Islamic religious education in the family environment plays a crucial role in forming the foundations of children's morals and spirituality from an early age, while religious education in the community functions as a reinforcement of social and moral values that support a harmonious community life based on Islamic principles. All this time, Islamic Religious Education (PAI) seems to be solely focused on educational issues, whereas an educator today faces different challenges. Challenges that are much greater than yesterday, so an Islamic Religious Education (PAI) educator must have a broad perspective. One of the most important challenges is the one affecting the Islamic economic system in this nation. Where practices of usury, embezzlement, fraud, and secularization are still heavily carried out by the Muslims themselves. This is the heavy task of PAI to form an Islamic society that will be able to create a family and community system that is Islamic and dignified in its Islam. Therefore, this writing attempts to offer answers to the skepticism and pessimism toward PAI. One of the discussions is related to the role of PAI in the family and society among Muslims.